Правове забезпечення реалізації форм місцевого управління - Токар Алла Миколаївна (My University, 2021)
Дисертацію присвячено комплексному аналізу форм місцевого управління. Розкрито сутність місцевого управління в системі соціального управління. Досліджено загальні підходи до визначення сутності форм управління при реалізації публічної влади. Визначено поняття форм місцевого управління та здійснена їх класифікація з використанням нового критерію. Висвітлено правове забезпечення реалізації структурних та функціональних форм місцевого управління. Проаналізовано поняття та ознаки структурних форм місцевого управління. Досліджено організаційно-правове забезпечення реалізації структурних форм взаємодії органів місцевого управління. Здійснено детальний аналіз актів місцевого управління як форми його прояву. Досліджено проблеми застосування адміністративного договору як форми місцевого управління. Встановлено необхідність розуміння місцевого управління як самостійного виду соціального управління, що здійснюється двома самостійними суб’єктами публічної влади на місцевому рівні. Закріплюючи за органами місцевого самоврядування певне коло питань місцевого значення, наділяючи їх юридично-владними повноваженнями та здійснюючи контроль за їх виконанням, держава визнає місцеве самоврядування як складову місцевого управління. Визначено поняття актів місцевого управління. Вказано на загальноприйняті ознаки актів управління (владність, односторонність волевиявлень місцевих органів виконавчої влади і органів місцевого самоврядування, їх посадових осіб), а також виділено спеціальні ознаки – спрямування їхнього спільного волевиявлення на врегулювання управлінських відносин адміністративно-територіальної одиниці чи вирішення конкретної управлінської справи та зафіксоване у встановленій законом формі. Внесено пропозиції як щодо вдосконалення чинного законодавства досліджуваної сфери, так і щодо змісту майбутніх законів «Про акти управління», «Про адміністративні договори». The dissertation is devoted to the complex analyses of the forms of local government. The main definitions of the category “local government” are investigated and broad and narrow approaches to understanding this phenomenon are analyzed. Local government is defined as the power-organizational activity of local executive authorities and local self-government bodies aimed at the development of important areas of public life within the administrative-territorial unit. The general approaches to the definition of the essence of the forms of government in the implementation of public authority are considered. Moreover, it has been established that local government is a type of social government, and on the other hand, it is a form of implementation of public power and by its nature is public administration, since it is aimed at ensuring public interest – local, which is integrated into the state. By means of revealing the essence of local government and the forms of the administrative activity whilst realizing the public power, the content of the forms of the administrative activity of the subjects of local administration has been researched By defining the nature of local government and forms of management activities in the implementation of public power, the essence of the forms of management activities of local government entities is investigated. It has been established that the forms of local government are a complex category that should characterize local government from the standpoint of the structural structure of local government bodies and their constituent units, the process of interaction between them and the external expression of the results of such interaction, as well as the external expression of the results of any management activities of these bodies. The structural-functional criterion of classification of forms of local government is offered. The concept of structural form of local government as an external expression of normatively established ways of building local executive bodies and local governments, as a whole, and their structural units, taking into account the ways of interaction between them.The main factors influencing the structural form of local government are identified. It is proved that the specificity of the structural form of local government is due to the state and self-governing nature of local government, the lack of vertical subordination and the competence of local government. The concept of the functional form of local government is formulated as an external expression of the normatively regulated activity of local government entities, which is manifested in the system of interconnected, arranged in a certain order of actions and their results. In the system of functional forms of local government we distinguish functional forms of local executive bodies, functional forms of local governments and functional forms of their interaction, which have an external expression in management acts and administrative agreements. The general properties of local government acts are revealed. The species diversity of local government acts has been studied and their classification by legal nature has been improved. The problems of concluding an administrative contract as a form of local government are studied. In scientific work the features of structural and functional forms are investigated in the interaction of local government bodies. The proposals related to the improvement of the current legislation in the researched sphere and to the contents of the future laws of Ukraine «On Acts of Administration», «On Administrative Agreements» have been made.